Fetal Annular Pancreas: Prenatal Ultrasonographic Diagnosis - Danaci, M.; Yayla, M.; Korkmaz, S.T.; Parildar, M.; Senalp, M. (My University, 1997)
Fetal duodenal obstruction is very rare and it can be diagnosed with ultrasonography in prenatal period. Early diagnosis and surgery treatment are very important for prognosis. We report that radiological and clinical findings of a case that is diagnosed as duodenal obstruction with ultrasonography. Annular pancreas was detected after surgery.
Fetal Annüler Pankreas: Prenatal Ultrasonografik Tanı
Keywords: Fetal Annular Pancreas; Prenatal Diagnosis; Ultrasonography